2007
DOI: 10.1016/s1571-0866(07)80050-9
|View full text |Cite
|
Sign up to set email alerts
|

25. Climate variability of the last five isotopic interglacials: Direct land-sea-ice correlation from the multiproxy analysis of North-Western Iberian margin deep-sea cores

Abstract: The last five isotopic interglacials (marine isotope stages 11, 9, 7, 5 and 1) were investigated in Iberian margin deep-sea cores, using terrestrial (pollen) and marine (planktic foraminifera assemblages, benthic and planktic oxygen isotopes) climatic indicators. This work shows that the climatic variability detected on the continent is contemporaneously recorded in the ocean, but temperature changes are not in phase with ice volume variations. The comparison of the different marine isotope stages highlights a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 37 publications
(41 reference statements)
3
22
0
1
Order By: Relevance
“…4) Bussell and Pillans (1992), Bradley (1999Bradley ( , 2015, and Siddall et al (2007) labeled the earliest peak in MIS 9 as MIS 9c, whereas Tzedakis et al (1997) designated that peak as MIS 9e, and it was subsequently identified as MIS 9e on the Quaternary chronostratigraphical charts of Gibbard and Cohen (2008) and Cohen and Gibbard (2011) and in Fig. 25.3 of Desprat et al (2007). On the other hand, Fig.…”
Section: Extension Of Lettered Substages To Time Other Than Mis 5 Anmentioning
confidence: 98%
See 1 more Smart Citation
“…4) Bussell and Pillans (1992), Bradley (1999Bradley ( , 2015, and Siddall et al (2007) labeled the earliest peak in MIS 9 as MIS 9c, whereas Tzedakis et al (1997) designated that peak as MIS 9e, and it was subsequently identified as MIS 9e on the Quaternary chronostratigraphical charts of Gibbard and Cohen (2008) and Cohen and Gibbard (2011) and in Fig. 25.3 of Desprat et al (2007). On the other hand, Fig.…”
Section: Extension Of Lettered Substages To Time Other Than Mis 5 Anmentioning
confidence: 98%
“…In their text, Bühring et al (2004) innovated further by using substage designations with two decimal-style dots, as in their substages 5.3.1 and 5.3.3. In a more complex hybrid, Jahns et al (1998) combined decimal-style numbers and letters in identifying single substages when they referred to "d 18 O-substage 12.2h", and Desprat et al (2007) combined lettered and numbered substages (e.g., 8.2, 9e, and 11.3) in one series in their Fig. 25.3.…”
Section: Hybridization and Modification (~1990 To Present)mentioning
confidence: 99%
“…For example, discrepancies exist between marine records on the existence of a northern temperature reversal during Termination II (Sarnthein and Tiedemann, 1990;Adkins et al, 1997;Chapman and Shackleton, 1998;Oppo et al, 2001;Kelly et al, 2006;Desprat et al, 2007;Weldeab et al, 2007). The establishment of the peak interglacial warmth at high northern latitudes during the LIG also remains controversial.…”
Section: A Govin Et Al: Early Last Interglacial Climate and Ice Shementioning
confidence: 99%
“…Spores and aquatic pollen percentages were obtained from the total sum including pollen, spores, indeterminables and unknowns. We have defined the major forested phases as periods showing a classical tree succession which is known in Southern Europe and in particular in NW Iberia for beginning with the development of Betula, deciduous Quercus, and ending by the expansion of late successional trees such as Carpinus betulus and Fagus (Tzedakis et al, 2001;Desprat et al, 2007). Local names are given to these major forested periods.…”
Section: Pollen Analysismentioning
confidence: 99%